Science, technology, engineering, and mathematics (STEM) education in university: pre-service teachers’ perceptions / Teoh Sian Hoon ... [et al.] - Teoh, Sian Hoon; Narayanan, Geethanjali; Syed Aris, Sharipah Ruzaina; Ibrahim, Norezan; Isa, Badrul (Universiti Teknologi MARA, 2022)
Science, Technology, Engineering, and Mathematics (STEM) education, an integration of the four disciplines, has been promoted in schools and universities in Malaysia. However, the teachers’ readiness in applying STEM has been an apprehension of not only the school administrators, but also the public. The implementation of STEM is observed from the teachers' abilities to organize learning environments that are created to strengthen students’ 21st-century skills. As such, the teachers' ability to implement and execute the plan are a concern. Thus, the aim of this study is to identify and evaluate preservice teachers' perceptions of their readiness, experiences, and effort in practising STEM education, as well as their degree of confidence in STEM education teaching and learning. A correlational research design was employed in this research to collect data from 113 science-based pre-service teacher trainees in a public university in Malaysia. The participants answered the questionnaire on their perceptions of their experiences and confidence level in learning STEM skills in their university courses and their views towards activities on STEM. Reflecting on the findings, this study has implications for the pre-service teacher trainees (students), faculty and organization as a whole in the preparation towards the execution of STEM in terms of strategies and intervention in school. This is especially advantageous for the university to raise awareness of the benefits of university STEM-related programs to a diverse background of students.